The physical and chemical characteristic of recycled concrete aggregate for removal phosphorus as a filter system - Abd Roni, Norwardatun; Adnan, Suraya Hani; Hamidon, Nuramidah; Tuan Ismail, Tuan Noor Hasanah (Penerbit UTHM, 2021)
The removal of phosphorus from wastewater is a common procedure. Improving water quality is the aim of wastewater treatment. There are many types of conventional methods that have been used for the removal of phosphorus. Phosphorus reaction with chemicals can be removed immediately from water. However, the use of chemicals often increases the cost of wastewater treatment. This study aims to investigate the physical and chemical characteristics of RCA that influence the removal of phosphorus, as well as the percentage of phosphorus removal using RCA of two different sizes namely, 5 mm to 10 mm and 25 mm to 30 mm. The samples taken from the influent and effluent filters were tested and analysed in terms of the uptake capacity of phosphorus (q) and the percentage of phosphorus removal (%). The highest percentage of phosphorus removal achieved was 99.54% in the initial concentration of 10 mg/L by RCA measuring between 5 mm to 10 mm while the lowest percentage of phosphorus removal was 66.25% in the initial concentration of 50 mg/L for RCAs measuring between 25 mm to 30 mm. Furthermore, RCA achieved the highest uptake capacity (q) of 3.45 mg/L in the initial wastewater concentration of 50 mg/L. In conclusion, RCA has the potential to remove phosphorus, particularly in low concentrations of synthetic wastewater and high pH conditions.